PENGARUH PH AIR MEDIA TERHADAP DAYA TETAS TELUR IKAN PATIN SIAM (PANGASIONODON HYPOPTHALMUS) - NI KADEK PUJI ASTUTI; AZHARI TARMIZI; MUHAMMAD IKROMIN (Universitas Mahasaraswati K. Mataram, 2023)
Water pH is an important external factor for the success of hatching fish eggs. PH stimulates the chorionase enzyme to be more active, it can soften the egg chorion. The purpose of this study was to determine the optimum pH value for Pangasianodon hypophthalmus hatching eggs. This research was conducted at the Batu Kumbung Fish Seed Installation, Lingsar, West Lombok. The research design used a completely randomized design with 5 treatments and 3 replications. Treatments are P1 (pH6), P2 (pH7), P3 (pH8), P4 (pH9) and P5 (pH10). The results showed that the different pH values of the water had a significant effect on the hatching percentage and the survival of Siamese catfish larvae. The highest hatching percentage (77.54%) was in the pH 8 treatment, the highest Siamese catfish larvae survival rate (95.12%) was in the pH 7 treatment which was not significantly different from pH 8 which produced 94.54%.